Studies on Schismatoglottideae (Araceae) of Borneo XIII: A Revision of the Schismatoglottis nervosa Species Complex - Wong, Sin Yeng (Singapore Botanic Garden, 2010)
A revision of the Schismatoglottis nervosa Ridl. species complex is presented. Ten species are recognized, of which three species are pre-existing (S. nervosa, S. elegans A.Hay, and S. brevicuspis Hook.f.) and seven are novel and described here (Schismatoglottis adoceta S.Y. Wong, S. linae S.Y. Wong, S. matangensis S.Y.Wong, S. simonii S.Y.Wong, S. tessellata S.Y. Wong, S. turbata S.Y. Wong, and S. ulusarikeiensis S.Y. Wong.) The S. nervosa species complex is readily delimitated by the pungent terpenoid smell when the vegetative tissues are crushed, and by the presence of longitudinally ridged petioles. A key to the S. nervosa species complex is presented and all species are illustrated.